Tata Cara Berkomunikasi Terkait Waktu dan Jam dalam Bahasa Inggris - Mutiara Dewi Lestari; Annisa Regina Maharani; Dina Anggreyani; M. Fauzi Ramadani; Lutfia Eka Ramadhani; Mar'atul Habibah; Anggi Saputra (Indo Publishing, 2025)
In this article, we comprehensively discuss the correct methods and rules for communicating about time and clocks in English. Mastery of this subject is crucial for effective daily and professional communication. The discussion covers various aspects, starting with the formal ways of telling the time (o'clock, quarter past, half past, quarter to) and the informal ways (using past and to), including the differences and contexts of their usage. Furthermore, the article elaborates on the use of the 12-hour format (AM/PM) and the 24-hour format (military time), along with the conversion rules and appropriate situations for each format. Additionally, it discusses common time-related phrases (for example, at noon, at midnight, in the morning, on time, in time), the correct usage of time prepositions (at, on, in), and how to ask for and reply to questions about time. The objective of this article is to provide a practical and structured guide so that readers can speak and write about time in English accurately and confidently.